Illegal Drug Use among Female University Students in Slovakia - Matejovičová, Barbora; Trandžík, Jozef; Schlarmannová, Janka; Boledovičová, Mária; Velemínský, Miloš (International Scientific Literature, Inc., 2015)
This study is focused on the issue of illegal drug use among female university students preparing to become teachers. The main aim was to determine the frequency of drug abuse in a group of young women (n=215, mean age 20.44 years). Using survey methods, we determined that 33.48% of female university students in Slovakia use illegal drugs and 66.51% of students have never used illegal drugs. Differences between these groups were determined using statistical analysis, mostly in 4 areas of survey questions. We determined that education of parents has a statistically significant influence on use of illegal drugs by their children (c2=10.14; P<0.05). Communication between parents and children and parental attention to children have a significant role in determining risky behavior (illegal drug use, c2=8.698, P<0.05). Parents of students not using illegal drugs were interested in how their children spend their free time (68.53%). We confirmed the relationship between consumption of alcohol and illegal drug use (c2=16.645; P<0.001) and smoking (c2=6.226; P<0.05). The first contact with drugs occurs most frequently at high school age. The most consumed “soft” drug in our group of female university students is marijuana. Our findings are relevant for comparison and generalization regarding causes of the steady increase in number of young people using illegal drugs.
Keywords: Drugs; Essential; Marijuana Smoking; Students; Women